PENGAMALAN DAN PENGALAMAN IBADAH SUNAH PENDIDIK UNTUK MEWUJUDKAN PENDIDIKAN BERBASIS KARAKTER - Lutfiyah, Lutfiyah (Tarbiyah, 2014)
Teacher is an example for his student. What the teacher needs is not only capably in the material, but also escorted by the loyalty of his religion. Because, his religiousness will appear from his characteristics. Honest is one of characteristic should teacher has. If the teacher is honest then the students will also be honest, if the teacher lying then students will not hesitate to lie, like the proverbial said that if the teacher take a pee by standing then student will do it by running. Similarly, it shown by teacher of RobbaniIslamic Elementary School in Kendal Regency, Central Java. As teachers who want their students to be noble human, useful for the nation and religion they equip themselves with the daily worship.Key Word: Honest, Robbani Islamic Elementary School, Character